DEVELOPMENT OF AGRICULTURAL EDUCATION IN AGRO INNOVATION PARK - Amanda Amelia Ismail; Riza Firmansyah; Tika Tresnawati (Journal of Tourism Destination and Attraction, 2022)
Tourism activities are not only to spend free time and vacation to relieve fatigue, but also increase knowledge and gain educational insight outside public schools. Efforts to meet these interests then formed a recreation area in which there is an element of edutourism. Edutourism is a mixture of tourism and educational activities. One of the places that provides educational tours is the Agro Innovation Park or commonly called Tagrinov. Tagrinov must revive sensations and experiences that can generate interest in revisiting tourists after being satisfied by previous visits, because the experience felt by tourists is one of the considerations for visitors when choosing tourism activities, therefore the measurement of experience can be measured by Experiential Marketing which includes components Sense, Feel, Think, Act, Relate